Question about Apple Computers & Internet

Ad

Hi,

a 6ya Technician can help you resolve that issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repair professionals here in the US.

click here to Talk to a Technician (only for users in the US for now) and get all the help you need.

Goodluck!

Posted on Jan 02, 2017

Ad

Well, Tom is 3 x 5 = 15 yrs now. Sam has 15 yrs to go to 20. Then Tom will be 15 + 5 = 30 yrs.

Or, Tom is 10 yrs older than Sam now, so when Sam is 20........

Or, Tom is 10 yrs older than Sam now, so when Sam is 20........

May 15, 2015 | GPS

Let x be the smallest number.

Let x + 2 be the other number (consecutive even integer)

Now to translate the rest;)

three times the smaller 3(x)

19 more -19

sum of the two integers - (x) +( x+2)

Pulling it together,

3x -19 = x + x +2

collect like terms

3x - 19 = 2x + 2

Put all the constants on one side by adding 19 to both sides.

3x - 19 +19= 2x + 2 + 19

3x = 2x +21

Subtract 2x from both sides to have all the x's on one side.

3x - 2x = 2x +21 - 2x

x = 21

The other number is 21 + 2, or 23

Check:three times the smaller = 3 x 21 = 63

sum of the two integers = 21 + 23 or 44

is 63 at least 19 more than 44

Let x + 2 be the other number (consecutive even integer)

Now to translate the rest;)

three times the smaller 3(x)

19 more -19

sum of the two integers - (x) +( x+2)

Pulling it together,

3x -19 = x + x +2

collect like terms

3x - 19 = 2x + 2

Put all the constants on one side by adding 19 to both sides.

3x - 19 +19= 2x + 2 + 19

3x = 2x +21

Subtract 2x from both sides to have all the x's on one side.

3x - 2x = 2x +21 - 2x

x = 21

The other number is 21 + 2, or 23

Check:three times the smaller = 3 x 21 = 63

sum of the two integers = 21 + 23 or 44

is 63 at least 19 more than 44

Feb 19, 2015 | Office Equipment & Supplies

Let Adjoa's age be x and Kwame's y.

- Adjoa is 3 years older than Kwame: x=y+3
- Seven years ago sum of their ages was 13: (x-7)+(y-7)=13
- Now you substitute first equation into second equation: (y+3-7)+(y-7)=13
- 2y-4-7=13
- 2y=24
- y=24/2=12 years
- x=y+3=12+3=15 years
- sum of their present ages is x+y=12+15=27 years

Sep 27, 2011 | Office Equipment & Supplies

Let m be Marian's age, d Diana's age and c Carlos age.

I hope I helped :)

- sum of ages is 17: m+d+c=17
- two years from now Marian will be twice as old as Diana: m+2=2*(d+2) so m+2=2d+4 so 2d=m-2 or d=(m-2)/2=m/2-1
- Carlos will be half as old as Marian 4 years from now: c+4=1/2(m+4) or c+4=m/2+2 or c=m/2-2
- now: m+d+c=m+m/2-1+m/2-2=17
- 2m=17+3=20
- m=20/2=10 years
- d=m/2-1=5-1=4 years
- c=m/2-2=5-2=3 years

I hope I helped :)

Sep 18, 2011 | Office Equipment & Supplies

Jan is 48 years old and Jake is 24 years old.

(Jan - N, Jake - K N=2K N+K=5K-48 N+K+48=5K N+48=4K N+48=2N 48=N K=N/2=48/2=24)

Thanks, that was fun.

(Jan - N, Jake - K N=2K N+K=5K-48 N+K+48=5K N+48=4K N+48=2N 48=N K=N/2=48/2=24)

Thanks, that was fun.

Jul 26, 2011 | Washing Machines

Three unknowns with three equasions:

cindy is 5 years older than alex. write it as c = a + 5

cindy is 7 years older than peter. write it as c = p + 7

The sum of their ages is 21. write it as c + a + p = 21

first solve for peters age in terms of alex's age.

c = p + 7 or

(a + 5) = p + 7 or

p = (a + 5) - 7 or

p = a - 2

substitute in and solve the equasion:

(a + 5) + a + (a - 2) = 21 or

3a + 3 = 21 or

3a = 24 or

a = 8

c = a + 5 or

c = 8 + 5 = 13

c = p + 7 or

p = c - 7 or

p = 13 - 7 = 6

cindy is 13, alex is 8 and peter is 6

This is called simultaneous equasions and will always work if you have the same number of unknowns as you have equasions (or relationships).

cindy is 5 years older than alex. write it as c = a + 5

cindy is 7 years older than peter. write it as c = p + 7

The sum of their ages is 21. write it as c + a + p = 21

first solve for peters age in terms of alex's age.

c = p + 7 or

(a + 5) = p + 7 or

p = (a + 5) - 7 or

p = a - 2

substitute in and solve the equasion:

(a + 5) + a + (a - 2) = 21 or

3a + 3 = 21 or

3a = 24 or

a = 8

c = a + 5 or

c = 8 + 5 = 13

c = p + 7 or

p = c - 7 or

p = 13 - 7 = 6

cindy is 13, alex is 8 and peter is 6

This is called simultaneous equasions and will always work if you have the same number of unknowns as you have equasions (or relationships).

Sep 20, 2009 | Puzzle Toys

X+X+28=4(X+X)

2X+28=4X+4X

28=8X-2X

28=6X

X=4

The twins are 4 yrs. old. The mother is 32.

Do I pass?

2X+28=4X+4X

28=8X-2X

28=6X

X=4

The twins are 4 yrs. old. The mother is 32.

Do I pass?

Apr 21, 2009 | Mathsoft StudyWorks! Mathematics Deluxe...

Standard deviation is the average root mean squared deviation from the average of the numbers.

Familiarize yourself with the wikipedia page on standard deviation: http://en.wikipedia.org/wiki/Standard_deviation

In this case, your question is easy. The standard deviation is 0, so this means the boys ages are all the same.

So they're all 24/3 = 8 years old.

Proof:

8 + 8 + 8 = 24 <-- satisfies the constraint that the boys ages must total to 24.

Get the standard deviation of these numbers;

8+8+8 / 3 = 8 <-- the average value is 8

The deviation of each boy's age from the average is:

boy 1

--------

8 years old, which deviates from 8 by 0

boy 2

--------

8 years old, which deviates from 8 by 0

boy 3

--------

8 years old, which deviates from 8 by 0

So the deviations are 0, 0 and 0.

To get the standard deviation, you sum the squares of the deviations of each boy, get the average, and square root. So:

0² + 0² + 0² = 0

Average is 0 / 3 = 0

Square root of 0 = 0

So the standard deviation is 0. Which shouldn't be much of a surprise to you. We just had to actually DO the work to show that it was in fact 0.

Familiarize yourself with the wikipedia page on standard deviation: http://en.wikipedia.org/wiki/Standard_deviation

In this case, your question is easy. The standard deviation is 0, so this means the boys ages are all the same.

So they're all 24/3 = 8 years old.

Proof:

8 + 8 + 8 = 24 <-- satisfies the constraint that the boys ages must total to 24.

Get the standard deviation of these numbers;

8+8+8 / 3 = 8 <-- the average value is 8

The deviation of each boy's age from the average is:

boy 1

--------

8 years old, which deviates from 8 by 0

boy 2

--------

8 years old, which deviates from 8 by 0

boy 3

--------

8 years old, which deviates from 8 by 0

So the deviations are 0, 0 and 0.

To get the standard deviation, you sum the squares of the deviations of each boy, get the average, and square root. So:

0² + 0² + 0² = 0

Average is 0 / 3 = 0

Square root of 0 = 0

So the standard deviation is 0. Which shouldn't be much of a surprise to you. We just had to actually DO the work to show that it was in fact 0.

Feb 08, 2008 | Audio Players & Recorders

Feb 20, 2018 | Apple Computers & Internet

86 people viewed this question

Usually answered in minutes!

×